Patients' experiences following local–regional recurrence of thyroid cancer: A qualitative study. Issue 1 (26th April 2013) - Misra, Shikha; Meiyappan, Soumia; Heus, Lineke; Freeman, Jeremy; Rotstein, Lorne; Brierley, James D.; Tsang, Richard W.; Rodin, Gary; Ezzat, Shereen; Goldstein, David P.; Sawka, Anna M.
Abstract Background and Objective The psychosocial impact of local–regional thyroid cancer recurrence is not known. The aim of this study was to explore thyroid cancer patients' experiences relating to diagnosis and treatment of local–regional disease recurrence. Methods We conducted 15 semi‐structured interviews with survivors of differentiated thyroid cancer who underwent neck reoperation for recurrent disease. Participants were recruited from the clinical practices of thyroid surgeons and endocrinologists at University Health Network and Mount Sinai Hospitals in Toronto, Ontario. Participant interviews were audio‐recorded, transcribed verbatim, and analyzed using qualitative methods. Saturation of themes was achieved. Results Local–regional recurrence of thyroid cancer was associated with significant psychological distress. Confidence in healthcare providers as well as psychosocial support from family or social relations, were helpful in coping with disease recurrence. After recovery from treatment, post‐traumatic growth was reported. However, questions and worry about the risk for future recurrence lingered at follow‐up. Conclusions Local–regional recurrence of thyroid cancer has a significant psychosocial impact on patients, and support needs are heightened throughout the experience. Healthcare providers should strive to ensure that medical information and psychosocial needs of such patients are met, throughout the treatment experience, as well as at follow‐up. J. Surg. Oncol. 2013;108:47–51. © 2013 Wiley Periodicals, Inc.